Personal Branding Strategies on Social Media Platforms (Case Study of Gaming YouTuber Ari Kulgar and Badminton Influencer @bernika_ave) - Scheffer-Sumampouw, Carly Stiana; Serafin, Michelle; Fortuna, Christabella Angelique (Institut Komunikasi dan Bisnis LSPR, 2024)
Booming profession is intensively utilizing social media on the internet. Choice of job or career as gamer and influencer, is very popular among the young generation of Indonesia. This activity of promoting oneself through social media is called personal branding. This study discusses two subjects who have different careers, but both use social media intensively in their career journeys. The two selected key informants have fulfilled the category of unique and prominent influencers in their industries. The theory used is about impression management by Erving Goffman; then how Montoya's 8 laws of personal branding are applied by both subjects. Study limitations are that the researchers only discuss the